2002
DOI: 10.1159/000066583
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Different Stages of Chronic Venous Insufficiency and Leg Ulcer

Abstract: Background: Chronic venous insufficiency (CVI) is a frequent disease, reaching from mild ankle edema to severe venous leg ulcer. Previous studies have focused on the quality of life (QoL) in patients with leg ulcer, but not in patients with early forms of CVI nor stagerelated differences. Objective: To assess the quality of life in patients with CVI stages I, II, IIIa and IIIb (venous leg ulcer). Patients and Methods: Survey in a representative sample. 324 consecutive patients with different stages of CVI o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 9 publications
(6 reference statements)
0
15
0
1
Order By: Relevance
“…QoL was significantly improved in patients with healed leg ulcers. Contrary to Lindholm, there was not a higher proportion of men but of women being markedly affected by QoL reductions [Zschocke et al, 2002]. Basically, these data are also confirmed by Price [1996] and Smith et al [2000] who used variants of the SF-36 Health Survey in order to assess the QoL.…”
Section: Quality Of Life In Chronic Woundsmentioning
confidence: 57%
See 1 more Smart Citation
“…QoL was significantly improved in patients with healed leg ulcers. Contrary to Lindholm, there was not a higher proportion of men but of women being markedly affected by QoL reductions [Zschocke et al, 2002]. Basically, these data are also confirmed by Price [1996] and Smith et al [2000] who used variants of the SF-36 Health Survey in order to assess the QoL.…”
Section: Quality Of Life In Chronic Woundsmentioning
confidence: 57%
“…The ulcers were major factors reducing the work capacity of many patients. Augustin et al also noted corresponding limitations in a German-speaking population both with a disease-specific [Augustin et al, 1997;Zschocke et al, 2002] and a generic QoL questionnaire [Augustin et al, 1999a]. QoL was significantly improved in patients with healed leg ulcers.…”
Section: Quality Of Life In Chronic Woundsmentioning
confidence: 98%
“…17,25,26 This combined approach is considered to be the most complete approach for evaluation of the management of patients with CVD. 27 In conclusion, the present study confirmed that R. aculeatus, combined with HMC and AA, is effective in reducing the symptoms and physical signs of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, Though not as severe as leg ulceration, chronic venous disease can also be of high patient burden. Previous studies suggest that the degree of impairment in HRQoL correlates with the stage of CVI (20). Accordingly, early detection and treatment of venous complaints is of great importance for preserving quality of life and functional capability.…”
Section: Health-related Quality Of Life In Patients With Chronic Wounmentioning
confidence: 99%